Facile Low-Temperature Synthesis of Carbon Nanotube/ Nanohybrids with Enhanced Visible-Light-Driven Photocatalytic Activity - Yunlong Xie; Huanhuan Qian; Yijun Zhong; Hangming Guo; Yong Hu (International Journal of Photoenergy)
We demonstrate a facile and novel chemical precipitation strategy for the accurate coating of TiO2 nanoparticles on the surface of carbon nanotubes (CNTs) to form CNT/TiO2 nanohybrids, which only requires titanium sulfate and CNTs as starting materials and reacts in the alkaline solution at 60°C for 6 h. Using this process, the as-prepared hybrid structures preserved the good dispersity and uniformity of initial CNTs. Furthermore, the CNT/TiO2 nanohybrids show a broad blue luminescence at 469 nm and exhibit significantly enhanced photocatalytic activity for the degradation of rhodamine B (RhB) under visible-light irradiation, which is about 1.5 times greater than that of commercial Degussa P25 TiO2 nanoparticles. It is believed that this facile chemical precipitation strategy is scalable and its application can be extended to synthesize other CNT/oxide nanohybrids for various applications.